10. PENGARUH KEBERADAAN KOMITE MANAJEMEN RISIKO TERHADAP LUAS PENGUNGKAPAN SUKARELA - Purbawati, Dinalestari (FORUM, 2014)
This study consisted of two test models. The first test model investigated the association between board characteristics such as board size, and proportion of non-executive directors, as well as firm characteristics (e.g. organisational complexity, financial reporting risk, and leverage) on the existence of a risk management committee. The second test model investigated the association between the existence of a risk management committee on the extent of voluntary disclosure. This study is explanatory research used secondary data. Data was collected from the annual reports non-financial companies listed on the Indonesian Stock Exchange (BEI) the period 2008, 2009 and 2010. Analysis tools used in the first test model is a logistic regression model and a second test using OLS regression. The results showed that only the variable board size who have a significant positive effect on the existence of the risk management committee and the existence of the risk management committee has a significant positive effect on the extent of voluntary disclosure.